Coming in the Air: Hypoxia Meets Epigenetics in Pancreatic Cancer - Claudia Geismann; Alexander Arlt (Cells, 2020)
With a five-year survival rate under 9%, pancreatic ductal adenocarcinoma (PDAC) represents one of the deadliest tumors. Although the treatment options are slightly improving, PDAC is the second leading cause of cancer related death in 2020 in the US. In addition to a pronounced desmoplastic stroma reaction, pancreatic cancer is characterized by one of the lowest levels of oxygen availability within the tumor mass and these hypoxic conditions are known to contribute to tumor development and progression. In this context, the major hypoxia associated transcription factor family, HIF, regulates hundreds of genes involved in angiogenesis, metabolism, migration, invasion, immune escape and therapy resistance. Current research implications show, that hypoxia also modulates diverse areas of epigenetic mechanisms like non-coding RNAs, histone modifications or DNA methylation, which cooperate with the hypoxia-induced transcription factors as well as directly regulate the hypoxic response pathways. In this review, we will focus on hypoxia-mediated epigenetic alterations and their impact on pancreatic cancer.